2018
DOI: 10.1016/j.yclnex.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of admission serum 25-hydroxyvitamin D levels and clinical outcomes in critically ill medical patients

Abstract: The aim of this study was to determine the incidence of hypovitaminosis D and the correlation of admission serum 25hydroxyvitamin D (25-OHD) levels and clinical outcomes in critically ill medical patients. Methods: A prospective, observational study was conducted. All critically ill medical patients admitted to the medical ICU were recruited. Blood sampling for serum 25-OHD was taken within 24 h after ICU admission. The levels of 25-OHD were dichotomized into deficiency and sufficiency groups. A serum 25-OHD l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…In our previous study on neurosurgical ICU patients, we also found a negative correlation between APACHE II score and admission serum levels of 25-hydroxyvitamin D 6. Consistent with our results, Bhurayanontachai et al 40 showed that vitamin D levels were significantly correlated with the severity of the illness in medical patients who are critically ill. Chen et al also reported that ICU-hospitalized patients who had 25-hydroxyvitamin D deficiency had significantly higher APACHE II scores than those with 25-hydroxyvitamin D insufficiency or sufficiency 41. It has been well denominated that several factors including malnutrition, lack of exposure to sunlight, decreased renal hydroxylation, and increased tissue conversion of 25-hydroxyvitamin D to 1,25 hydroxyvitamin D may contribute to the vitamin D deficiency in long-stay patients who are critically ill.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study on neurosurgical ICU patients, we also found a negative correlation between APACHE II score and admission serum levels of 25-hydroxyvitamin D 6. Consistent with our results, Bhurayanontachai et al 40 showed that vitamin D levels were significantly correlated with the severity of the illness in medical patients who are critically ill. Chen et al also reported that ICU-hospitalized patients who had 25-hydroxyvitamin D deficiency had significantly higher APACHE II scores than those with 25-hydroxyvitamin D insufficiency or sufficiency 41. It has been well denominated that several factors including malnutrition, lack of exposure to sunlight, decreased renal hydroxylation, and increased tissue conversion of 25-hydroxyvitamin D to 1,25 hydroxyvitamin D may contribute to the vitamin D deficiency in long-stay patients who are critically ill.…”
Section: Discussionsupporting
confidence: 92%
“…This study proposed that a low level of sodium in these patients suggests heart failure severity [ 26 ], but it could also be a heart failure outcome. Diuretic consumption is one cause of drugs producing hyponatremia [ 27 ]. Our results indicated that some CCU patients had higher levels of sodium.…”
Section: Discussionmentioning
confidence: 99%